Respuesta :

AroJad

Answer:

3+n^2

Step-by-step explanation:

there is 3 added, then 5, then 7, then 9.

fichoh

The nth term of the quadratic sequence in the question is n² + 3

Given the sequence :

  • 4, 7, 12, 19, 28,....

The first difference ;

  • 7 - 4 ; 12 - 7; 19 - 12 ; 28 - 19 = 3, 5, 7, 9

The second difference ;

  • 5 - 3 ; 7 - 5 ; 9 - 7 = 2, 2, 2

Hence, second difference = 2

Half of the second difference, a = 2/2 = 1, hence, a = 1

3a + b = second term - first term

3a + b = 7 - 4

3a + b = 3

3(1) + b = 3

3 + b = 3

b = 3 - 3

b = 0

a + b + c = First term

1 + 0 + c = 4

c + 1 = 4

c = 4 - 1

c = 3

The nth term of a quadratic sequence can be expressed as :

Tn = an² + bn + c

Tn = 1(n²) + 0(n) + 3

Therefore, the nth term of the quadratic sequence is n² + 3

Learn more : https://brainly.com/question/22412845?referrer=searchResults